Effects of curcumin and its adjuvant on TPC1 thyroid cell line. (25th May 2019) - Esposito, Teresa; Lucariello, Angela; Hay, Eleonora; Contieri, Marcella; Tammaro, Pasquale; Varriale, Bruno; Guerra, Germano; De Luca, Antonio; Perna, Angelica
Abstract: Previous studies have demonstrated that different curcumin extracts are able to influence cell metabolic activity vitality in human papillary thyroid carcinoma TPC-1 cells. We continued the study using the most effective extract and adding other nutraceuticals such as piperine and vitamin E, in order to define the possible role of these in modulating the genetic expression of cell markers and to understand the effectiveness in modulating the regression of cancer phenotype. Cells were treated with one extract of curcumin (Naturex ® Ultimate Botanical Benefits), with Piperine (Piper Longum, A.C.E.F.) and Vitamin E (Dry Vitamin E-Acetate 50% DC, BASF) alone and in combination, dissolved in the culture medium, for 48 h. Treatment with the different nutraceuticals is able to influence cell cycle regulators (cyclin D1, β-catenin, p21, p53) and activators or inhibitors of apoptosis (BAX, pro-caspase3, Bcl-2). They are able to influence cell cycle distribution and metabolic activity vitality. The inhibitory effect of curcumin, piperine and vitamin E on cell proliferation involves different markers, and in particular inhibits β-catenin, cyclinD1 and p53, making them candidates for a possible use in alternative therapies although further studies are needed. Graphical abstract: Image 1 Highlights: Curcumin, peperin and vitamin E have the ability to inhibit the viability of TPC1 cells. After treatment, the TPC1 cells showed a blockage of the cell cycle in the G2/M phase. Curcumin, peperin and vitamin E induce chromatin condensations. The cell cycle regulators and activators or inhibitors of apoptosis were evaluated, observing a change in their modulation.